Urodynamic studies in children: Standardized transurethral video-urodynamic evaluation. Issue 1 (February 2016) - Spinoit, Anne-Françoise; Decalf, Veerle; Ragolle, Inge; Ploumidis, Achilles; Claeys, Tom; Groen, Luitzen-Albert; Van Laecke, Erik; Hoebeke, Piet
Summary: Objective: The aim was too demonstrate standardized video-urodynamic study (VUDS) in children using a transurethral catheter and pressure transducers. Methods: Data necessary to obtain urodynamic evaluation of bladder sphincter function were gathered by concomitant measurement of bladder, urethral, and abdominal pressure. A 7F transurethral triple-lumen water-filled catheter was used for measuring the bladder and sphincter pressures and a water-filled 8F catheter connected to a pressure transducer was inserted into the rectum for pressure measurement. Cystometry was combined with fluoroscopy, providing simultaneous voiding cystourethrography information. Detrusor activity, bladder sensation, capacity, and compliance were measured during filling cystometry. Voiding cystometry consisted of recording pressures in the bladder sphincter and abdomen with simultaneous urinary flow measurement. Results: Transurethral VUDS was safely and easily performed in a clinical setting adapted to children. Conclusions: A good and reproducible UDS is mandatory for correct therapeutic decisions. A standardized study associated with fluoroscopic assessment is presented in this video.